Integracion comercial del Caribe : problemas y perspectivas. - Griffith, Winston H. (1990)
Analyzes the impact of regional development based on direct foreign investment to supply the prevailing scarcity of capital in the region. Discusses the effects of the technological revolution on the region's growth and development. Its comparative advantage, which is at the same time the foundation of CARICOM, is to be found in its low cost of labour and the commodity exports. These factors will become less important in the world as a result of technological change.